Neoadjuvant chemoradiotherapy or chemotherapy alone for oesophageal cancer: population-based cohort study. Issue 4 (23rd March 2021) - Kamarajah, S K; Phillips, A W; Ferri, L; Hofstetter, W L; Markar, S R
Abstract: Background: Although both neoadjuvant chemoradiotherapy (nCRT) and chemotherapy (nCT) are used as neoadjuvant treatment for oesophageal cancer, it is unknown whether one provides a survival advantage over the other, particularly with respect to histological subtype. This study aimed to compare prognosis after nCRT and nCT in patients undergoing oesophagectomy for oesophageal adenocarcinoma (OAC) or squamous cell carcinoma (OSCC). Methods: Data from the National Cancer Database (2006–2015) were used to identify patients with OAC and OSCC. Propensity score matching and Cox multivariable analyses were used to account for treatment selection biases. Results: The study included 11 167 patients with OAC (nCRT 9972, 89.3 per cent; nCT 1195, 10.7 per cent) and 2367 with OSCC (nCRT 2155, 91.0 per cent; nCT 212, 9.0 per cent). In the matched OAC cohort, nCRT provided higher rates of complete pathological response (35.1 versus 21.0 per cent; P  < 0.001) and margin-negative resections (90.1 versus 85.9 per cent; P  < 0.001). However, patients who had nCRT had similar survival to those who received nCT (hazard ratio (HR) 1.04, 95 per cent c.i. 0.95 to 1.14). Five-year survival rates for patients who had nCRT and nCT were 36 and 37 per cent respectively ( P  = 0.123). For OSCC, nCRT had higher rates of complete pathological response (50.9 versus 30.4 per cent; P  < 0.001) and margin-negative resections (92.8 versus 82.4 per cent; P  < 0.001). A statistically significant overall survival benefit was evident for nCRT (HR 0.78, 0.62 to 0.97). Five-year survival rates for patients who had nCRT and nCT were 45.0 and 38.0 per cent respectively ( P  = 0.026). Conclusion: Despite pathological benefits, including primary tumour response to nCRT, there was no prognostic benefit of nCRT compared with nCT for OAC suggesting that these two modalities are equally acceptable. However, for OSCC, nCRT followed by surgery appears to remain the optimal treatment approach. Abstract : Despite pathological benefits, including primary tumour response to neoadjuvant chemoradiotherapy (nCRT), there was no prognostic benefit from nCRT compared with neoadjuvant chemotherapy for oesophageal adenocarcinoma, suggesting that both modalities are equally acceptable. However, for oesophageal squamous cell carcinoma, nCRT followed by surgery appeared to remain the optimal treatment approach. Histology is the key